Pengaruh Perbedaan Lama Inkubasi Tanah yang Diaplikasi Kotoran Ayam terhadap Pertumbuhan dan Hasil Tanaman Sawi - Muhammad Ramadani Ilmiawan; Noorkomala Sari; Riza Adrianoor Saputra (Agroekotek View, 2026)
This study aimed to determine the effect of chicken manure incubation times on the growth and yield of mustard greens, as well as the optimal incubation time for mustard greens. The study was designed using a Completely Randomized Design (CRD). It consisted of five treatments and four replications, resulting in 20 experimental units. The five treatments were: H0 = no incubation (control)/0 days, H1 = incubation for 3 days, H2 = incubation for 7 days, H3 = incubation for 11 days, and H4 = incubation for 15 days. The experiment was conducted at the Greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, from February 2025 to April 2025.The results showed that the incubation period for chicken manure affected changes in soil chemical properties such as organic carbon, available phosphorus, available potassium, and pH. However, the incubation period did not affect most growth parameters, such as leaf number and leaf width. A 7-day incubation period (D2) provided the best results for several parameters, namely plant height and fresh weight, although it did not achieve the optimal growth characteristics of the Shinta F1 variety.